Survey of Sedation and Analgesia Practice Among Canadian Pediatric Critical Care Physicians*. Issue 9 (September 2016) - Garcia Guerra, Gonzalo; Joffe, Ari R.; Cave, Dominic; Duff, Jonathan; Duncan, Shannon; Sheppard, Cathy; Tawfik, Gerda; Hartling, Lisa; Jou, Hsing; Vohra, Sunita
Abstract : Background: Despite the fact that almost all critically ill children experience some degree of pain or anxiety, there is a lack of high-quality evidence to inform preferred approaches to sedation, analgesia, and comfort measures in this environment. We conducted this survey to better understand current comfort and sedation practices among Canadian pediatric intensivists. Methods: The survey was conducted after a literature review and initial focus groups. The survey was then pretested and validated. The final survey was distributed by email to 134 intensivists from 17 PICUs across Canada using the Research Electronic Data Capture system. Results: The response rate was 73% (98/134). The most commonly used sedation scores are Face, Legs, Activity, Cry, and Consolability (42%) and COMFORT (41%). Withdrawal scores are commonly used (65%). In contrast, delirium scores are used by only 16% of the respondents. Only 36% of respondents have routinely used sedation protocols. The majority (66%) do not use noise reduction methods, whereas only 23% of respondents have a protocol to promote day/night cycles. Comfort measures including music, swaddling, soother, television, and sucrose solutions are frequently used. The drugs most commonly used to provide analgesia are morphine and acetaminophen. Midazolam and chloral hydrate were the most frequent sedatives. Conclusion: Our survey demonstrates great variation in practice in the management of pain and anxiety in Canadian PICUs. Standardized strategies for sedation, delirium and withdrawal, and sleep promotion are lacking. There is a need for research in this field and the development of evidence-based, pediatric sedation and analgesia guidelines. Abstract : Supplemental Digital Content is available in the text.